Energy level modeling of lanthanide materials: review and uncertainty analysis1. Issue 29 (7th August 2015) - Joos, Jonas J.; Poelman, Dirk; Smet, Philippe F.
<x xml:space="preserve">Abstract</x> Empirical energy level models for describing lanthanide materials are reviewed and situated in a broader theoretical framework. The accuracy of determining experimental quantities through modeling is assessed.